2017
DOI: 10.1101/199059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brd4-bound enhancers drive cell intrinsic sex differences in glioblastoma

Abstract: Abstract:Sex differences in the incidence and severity of numerous human diseases, including cancer, are substantial and demand an understanding at a molecular level. In an established model of Glioblastoma (GBM), we discovered transcriptome-wide sexual dimorphism in patterns of gene-expression, H3K27ac marks (ChIP-seq) and large Brd4-bound enhancers (calling cards) of the type referred to as super/stretch enhancers. Genetic depletion or pharmacological inhibition of Brd4 reproducibly abrogated the sex differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…The same authors reported that sex differences in tumor phenotype are dependent on differential Brd4-bound enhancer regulation of stem cell–like phenotypes in male and female, both in mice and human GBM cells; and that inhibition of Brd4 resulted in decreased in vitro clonogenicity and in vivo growth of male tumors and opposite effects on female cells and tumors [ 113 ]. Sex-specific transcriptome expression in GBM patients has been studied recently.…”
Section: Disease Phenotypementioning
confidence: 99%
“…The same authors reported that sex differences in tumor phenotype are dependent on differential Brd4-bound enhancer regulation of stem cell–like phenotypes in male and female, both in mice and human GBM cells; and that inhibition of Brd4 resulted in decreased in vitro clonogenicity and in vivo growth of male tumors and opposite effects on female cells and tumors [ 113 ]. Sex-specific transcriptome expression in GBM patients has been studied recently.…”
Section: Disease Phenotypementioning
confidence: 99%
“…Unfused piggyBac has an insertion preference at super-enhancers which are a class of enhancers regulating genes linked to cell identity 45,46 . Leveraging this property, calling cards have been used to read out these important regulatory elements 3,16,47 . To record these sites in vivo , we co-transduced mouse cortexes with unfused piggyBac and barcoded or non-barcoded SRTs.…”
Section: Resultsmentioning
confidence: 99%
“…Further, insertion profiles can depend on chromatin state 50 so SRTs can potentially be used to read out chromatin status and histone modifications. For example, unfused piggyBac has an insertion preference at super-enhancers which are a class of enhancers regulating genes linked to cell identity 50,51 , and it has been used to read out these important regulatory elements 3,16,52 . Joint measurements of piggyBac insertions and gene expression with this method may help link super-enhancers to gene regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is not the first study providing evidence that novel anti-cancer therapeutics currently in clinical trials might have sex-specific effects. It was recently reported that clinically utilized bromodomain inhibitors could produce sex-specific responses (Kfoury et al, 2021). Together, these studies emphasize the importance of including sex as a variable in basic research and clinical settings.…”
Section: Discussionmentioning
confidence: 99%